BIOMETRIC ACCESS CONTROL SYSTEMS BASED ON FINGERPRINTS - V. V. Starovoitov (Informatika)
Features of biometric access control system design for control people's access to certain facilitiesare described. Basic algorithms for fingerprint processing and analysis are given in details. Construction schemes of three variants of an access control system are presented.